Guns and lightning: power law distributions in intrastate conflict intensity dynamics - Trinn, Christoph; Naumann, Lennard (Conflict management and peace science, 2022)
The discovery of power laws in conflict intensities has spurred numerous explanation attempts. Two different interpretations have persisted: the notion that power laws are spurious results of random processes and the opposing view that power-law distributions attest to endogenous dynamics linked to self-organized criticality (SOC). We substantiate the SOC forest-fire model for intrastate conflicts, conceptualizing conflict potential as social pressure, measured by horizontal inequality. This potential is triggered by infinitesimal events. Their occurrence depends on the interaction density between conflict actors, operationalized as the conjunction of state capacity and non-state governance. In a global analysis of 143 conflict dyads, we find that 40 conform to a power law and 33 to a stretched exponential distribution, the two outcomes predicted by the model. We find evidence that the forest-fire model is a plausible approximation of the dynamics of intrastate conflicts, accounting for both the conformity and the non-conformity to power laws.
Gesehen am 21.03.2023